INFLUENCIA DE LA MOTIVACION LABORAL EN EL CLIMA ORGANIZACIONAL DE DISFRUTA - HUANCAYO - Poves Varillas y Cols., Jessica Patrick (2019)
This research work, named “Influence of the work motivation in the organizational environment” let evaluate the DisFruta-Huancayo work motivation; based in a theoretical background that integrates: theoretical issues, internal context conditions influences and the laws that govern this context. Previous observations were done using the poll technique, using a questionnaire and having as informers the DisFruta-Huancayo workers, in order to diagnose the problems. The interview technique was also used.The applied model based in Maslow theory is divided in three parts, in  order to reach its objectives: in the first part DisFruta Huancayo workers were trained; in the second part the workers needs were evaluated, and it was found that the workers were not satisfied based on a previous analysis that take into account the attitudes and personalities of the workers for a better understanding, based on the collected data actions are applied, these actions generate satisfaction in the worker; at last, in the third part, the enterprise is evaluated based on the training knowledge and the needs reevaluation. It can be stated as a conclusion that work motivation in DisFruta workers was affected by applied empirics, lacks and deficiencies had a negative influence in the enterprise organizational environment. Because they do not respect or make a bad transmission of the work policies to reach the objectives, they do not know or are bad applied some theoretical issues related to this kind of research, or because it did not adequate to the conditions of the intern context. Problems that were solved with the methodological intervention, achieving in this way to improve the work motivation of the DisFruta Huancayo Workers, and this fact will be reflected in the organizational environment. Also is recommended, that the actions derived from this research could be maintained, in order to look for a continuous improvement of the Enterprise, besides, is recommended that it could be incorporated male gender workers, for furthering more dialog, harmony and equilibrium. In this way the adequate motivation that influences the organizational environment will also be improved.